"Aarogya Setu": The mobile application that monitors and mitigates the risks of COVID-19 pandemic spread in India. Issue 2 (November 2021) - Nagori, Viral
The case study demonstrates the journey of the 'Aarogya Setu' app - A contact tracing the mechanism developed in the form of a mobile application to monitor and mitigate the risk of COVID-19 pandemic spread in India. The case describes how Aarogya Setu mobile app works, how it identifies the hotspot areas, its features and privacy policies, and the reasons why the app had been in the news due to positive and negative perceptions of the citizens related to the app. However, the case can be used as a pedagogical tool for the various subjects in the discipline of Information Systems and Digital Technologies. The case helps to understand how to design and develop mobile application features and functions that protect individual privacy. In the end, the case throws challenging questions to the users on different aspects of gamification and m-governance.